IDEAL study: A real‐world assessment of pattern of use and clinical outcomes with recombinant coagulation factor IX albumin fusion protein (rIX‐FP) in patients with haemophilia B in Italy. Issue 1 (24th November 2022) - Tagliaferri, Annarita; Molinari, Angelo Claudio; Peyvandi, Flora; Coppola, Antonio; Demartis, Francesco; Biasoli, Chiara; Borchiellini, Alessandra; Cultrera, Dorina; De Cristofaro, Raimondo; Daniele, Filomena; Giordano, Paola; Marchesini, Emanuela; et al.
Abstract: Introduction: Factor IX replacement therapy is used for treatment and prophylaxis of bleeding in haemophilia B. rIX‐FP is an extended half‐life albumin‐fusion protein, which, in clinical studies, has demonstrated prolonged dosing intervals up to 21 days for routine prophylaxis, providing therapeutic benefit. Aims: To describe dosing frequency and consumption (primary endpoint), efficacy and safety of rIX‐FP treatment during routine clinical practice in Italy. Methods: Patients with moderate/severe haemophilia B on prophylaxis with rIX‐FP for ≥6 months, were enrolled in this observational study from October 2017 to February 2019 and followed‐up for 2 years. Descriptive analysis included prospective and retrospective data (12 months prior to switching to rIX‐FP). Results: Data were collected from 59 male patients (median age 30.1 years) enrolled by 23 Italian centres. Of them, 50 were on prophylaxis during the entire observation period and completed the study. The infusion frequency changed from 2–3 times/week in 86.0% of patients with previous treatment, to less than once a week in 84.0% of patients treated with rIX‐FP at the 2nd‐year follow‐up. The annual number of infusions decreased by about 70%, whereas the mean FIX activity trough level increased from 3.8% to 14.4% (mean > 10% in all the infusion regimens). Median Annualised Bleeding Rate of .0 was achieved across all prophylaxis regimens. Subjects with zero bleedings increased from 66.0% to 78.0% with rIX‐FP. Conclusion: Treatment with rIX‐FP reduced infusion frequency, while providing higher FIX trough levels with substantial benefit in terms of annualised bleeding rate and a good safety profile.